A hybrid current - Bashirullah, R. (IEEE Transactions on VLSI systems)
This brief describes an adaptive bandwidth bus architecture based on hybrid current/voltage mode repeaters for long global RC interconnect static busses that achieves high-data rates while minimizing the static power dissipation associated with current-mode (CM) signaling. An experimental adaptive bandwidth bus test chip fabricated in AMI 1.6-μm Bulk CMOS indicates a reduction in power dissipation of approximately 62% over CM sensing and an increase in maximum data rate of 40% over voltage-mode signaling.